The Impact of Strategic Behavior in Achieving Strategic Success: An Analytical Research of The Views of a Sample of Administrative Leaders in the CHF Cooperative Housing Institutions in The Middle Euphrates Region in Iraq - الجنابي رنا زاهر سلمان (Finance and Business Economies Review, 2023)
The research aims to determine the relationship of the impact of strategic behavior in achieving the strategic success of profit-making organizations through the realizations of a selected sample of administrative leaders working in cooperative housing institutions (CHF) in the Middle Euphrates region in Iraq, as the analytical descriptive approach was used to reach the results through the distribution of (100 ) A questionnaire form on a sample of administrative leaders, from which (85) forms valid for analysis were retrieved, and after collecting information and data and processing them statistically using the SPSSV25 program, the research came out with a set of conclusions, the most important of which was the existence of a correlation and influence of significant significance for strategic behavior in achieving strategic success, and therefore the research recommended The need for the organizations surveyed to identify the most important areas through which strategic success can be achieved and to employ that when choosing the appropriate strategic behavior.